Iron deficiency anaemia pathway: leveraging colonoscopy findings to predict panenteric capsule endoscopy outcomes with FIT as a triage tool: interim analysis of the CLEAR IDA multicentre study - Ian Io Lei; Nicola O'Connell; Michael Adu-Darko; Vishnupriya Suresh; Kiara Mcdonnell; Jessie Newville; Kirsten Chaplin; Omar Khalil; Deekshi Siyambalapityage; Asad Khan; Usman Muhammad; John Emil; et al. (Clinical Medicine)
Background: Iron deficiency anaemia (IDA) often prompts gastrointestinal investigations because of malignancy concerns. However, the diagnostic yield for significant gastric or colorectal pathologies is low, frequently resulting in repeated upper gastrointestinal (GI) endoscopy (OGD) and colonoscopy before small bowel evaluation in recurrent cases. Panenteric capsule endoscopy (PCE)/colon capsule endoscopy (CCE) provides a single-procedure solution for assessing the small bowel and colon, potentially streamlining diagnostics in a one-stop clinic. The Scotcap study found that 59% of CCE patients required follow-up procedures for therapeutics or completion, raising costs. The faecal immunochemical test (FIT) was introduced as a triage tool for identifying high-risk patients for direct colonoscopy, but its role in the IDA pathway with PCE remains insufficiently studied. Aim: This multicentre retrospective study evaluated the prevalence of significant polyps in IDA patients. It used NHS England CCE follow-up colonoscopy criteria to estimate the proportion requiring urgent follow-up colonoscopy if similar findings were observed with CCE. It also aimed to identify an optimal FIT threshold to minimise unnecessary reinvestigations. Method: 1,335 patients who underwent both OGD and colonoscopy between September 2023 and September 2024 from 3 UK centres were included. Data collected included haemoglobin, age, endoscopic findings, bowel preparation quality, repeat procedures and small bowel capsule use. NHS England CCE criteria were applied to predict urgent CCE-to-colonoscopy conversion (CCC) rates if CCE were the index test. Logistic regression, decision curve analysis and cost-benefit analysis were conducted to predict optimal FIT thresholds for PCE based on colonoscopy findings. Results: 671 (50.3%) patients had IDA, with 89% undergoing FIT before their procedures. Significant findings included 39 colorectal cancers (5.8%), 202 patients with polyps (30.1%), 10 cases of inflammatory bowel disease (1.5%), and 15 failed colonoscopies requiring computed tomography (CT) scans (2.2%). Only 12 patients (1.8%) required repeat tests or small bowel capsules. Extrapolating colonic findings to predict the CCC rate, FIT demonstrated an area under the curve (AUC) of 0.62. FIT thresholds of 10, 55 and 100 were associated with significant increases in CCC rates. Logistic regression revealed no difference in CCC rates between FIT thresholds of ≤10 and 11–55, but showed significant differences in CCC rates for FIT 56–100 (p=0.024) and FIT >100 (p=0.0044). The cost–benefit analysis identified FIT 10 as the threshold where net benefit shifted from positive to negative because of CCC. At this threshold, the CCC rate was 7.9%, based solely on identified pathologies, excluding poor bowel preparation and incomplete procedures. Conclusion: Significant pathologies in the IDA pathway were uncommon. A FIT threshold in the range of 10–55 was identified as a desirable target for CCE to minimise CCC rates, with full results pending.